2002
DOI: 10.1021/la015692z
|View full text |Cite
|
Sign up to set email alerts
|

Orientation in Methyl- and Hydroxyl-Terminated Self-Assembled Alkanephosphate Monolayers on Titanium Oxide Surfaces Investigated with Soft X-ray Absorption

Abstract: Titanium oxide surfaces were coated with methyl-and hydroxyl-terminated dodecyl phosphate monolayers by immersion of the substrates into aqueous solutions of the corresponding ammonium salts (DDPO4-(NH4)2 and OH-DDPO4(NH4)2). The samples were examined by contact-angle measurements and nearedge X-ray absorption fine structure spectroscopy. DDPO4 was found to form self-assembled films of comparable quality to those of the longer octadecyl phosphate prepared from an organic solvent and to those of a similar thiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 35 publications
6
54
0
1
Order By: Relevance
“…It seems quite reasonable to continue searching for more efficient corrosion inhibitors of this class, including those for other metals and alloys, in the near future. For example, S. Tosatti et al [44,45] studied the monolayers formed in 48 h in aqueous solutions of ammonium salts of DDP and hydroxy-dodecyl phosphate (HDDP) on smooth and rough surfaces of Ti and TiO 2 . They found that on smooth surfaces the monolayers of DDP were densely packed, which provided hydrophobization of the surface (contact angle  = 110°), but the surface remained hydrophilic ( = 10-50°) after HDDP adsorption.…”
Section: Organic Esters Of Phosphoric Acidmentioning
confidence: 99%
“…It seems quite reasonable to continue searching for more efficient corrosion inhibitors of this class, including those for other metals and alloys, in the near future. For example, S. Tosatti et al [44,45] studied the monolayers formed in 48 h in aqueous solutions of ammonium salts of DDP and hydroxy-dodecyl phosphate (HDDP) on smooth and rough surfaces of Ti and TiO 2 . They found that on smooth surfaces the monolayers of DDP were densely packed, which provided hydrophobization of the surface (contact angle  = 110°), but the surface remained hydrophilic ( = 10-50°) after HDDP adsorption.…”
Section: Organic Esters Of Phosphoric Acidmentioning
confidence: 99%
“…So, modifying the implant surface through phosphonic groups appears to be a way to promote a strong adhesion between the implant surface and bone tissue. Improvement of corrosion resistance is additionally obtained by this type of organic modification [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Formation of very stable organophosphonic acid monolayer on aluminum alloys covered with an amorphous thin oxide film has been reported in many studies (e.g., [80,85,86] [96]. It has been shown that alkylphosphonate SAMs on TiO 2 surface had comparable packing densities to those of alkanethiols on gold, and similar inclinations of the alkyl chains as well [97]. Tambe and Bhushan characterized the nanotribological properties of alkylsilane and perfluoroalkylsilane SAMs on Si(100) and alkylphosphonate SAMs on Al and found that alkylphosphonate SAMs exhibited lower coefficients of friction but comparable adhesive forces compared to the alkylsilane SAMs with the same alkyl chain lengths [93].…”
Section: Interactions Between Head Groups and Substrate Surfacesmentioning
confidence: 68%